Analysis of Comment Features of the Skintific Account on TikTok - Aprilianne, Vanya Cindy; Agustini, Maria Yosephine Dwi Hayu (Universitas Pendidikan Indonesia, 2024)
This study aims to analyze the comment features of the Skintific account on TikTok, a skincare brand that has gone viral on the platform, in order to identify positive comments that can influence sales. The data on comment are comments posted during the period of twin date, collected and analyzed qualitatively with a focus on classifying them according to the sentiment positive, neutral, and negative, and on identifying the main idea. The results show that most of the comments were positive, while some were neutral and only a small number were negative. The main idea were predominantly comments on product satisfaction and product effectiveness. Majority of positive comments related to the experience of using the product. The analysis also highlighted that neutral comments relate to the importance of interaction in particularly recommendations on product usage as an opportunity to increase consumer engagement and knowledge. For Skintific, understanding consumer sentiment and focusing on positive testimonials are the key in designing more effective marketing strategies that are responsive to consumers’ needs. In addition, addressing negative comments and spam is also necessary to maintain a positive brand image on the TikTok platform.